Penerapan Aerator Tenaga Surya dan Digitalisasi Pencatatan Usaha untuk Meningkatkan Produktivitas Pembudidaya Ikan di Pokdakan Mina Jaya, Banyumas - Yuliantoro, Prasetyo; Munang, Aswan; Putra Rakhmadani, Diovianto (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
The Fish Farming Group (Pokdakan) Mina Jaya in Banyumas Regency faces challenges related to low dissolved oxygen (DO) levels in earthen ponds and the lack of structured business documentation. To address these issues, a community service team from Telkom University Purwokerto implemented a solar-powered aerator system equipped with automatic control based on DO sensor readings and provided training on digital business recording. The program applied a participatory approach, including initial coordination, technology installation, training sessions, and impact monitoring. The results show that the aerator system successfully increased the stocking capacity from 2,000 to 3,000 fish per pond without a significant rise in mortality rate. Additionally, the digital bookkeeping training was adopted by some members using simple spreadsheet tools. These outcomes indicate that the application of appropriate technology and basic digitalization can offer practical solutions to improve the productivity and efficiency of small-scale fish farming operations. This program also demonstrates strong potential for replication in other communities with similar conditions.